A review and bibliometric analysis of the current studies for the 6G networks - Salih, Qusay M.; Rahman, Md. Arafatur; Ahmad Firdaus, Zainal Abidin; Jassim, Mohammed Rajih; Kahtan, Hasan; Jasni, Mohamad Zain; Ali, Ahmed Hussein (Tech Science Press, 2024)
The race to develop the next generation of wireless networks, known as Sixth Generation (6G) wireless, which will be operational in 2030, has already begun. To realize its full potential over the next decade, 6G will undoubtedly necessitate additional improvements that integrate existing solutions with cutting-edge ones. However, the studies about 6G are mainly limited and scattered, whereas no bibliometric study covers the 6G field. Thus, this study aims to review, examine, and summarize existing studies and research activities in 6G. This study has examined the Scopus database through a bibliometric analysis of more than 1,000 papers published between 2017 and 2021. Then, we applied the bibliometric analysis methods by including (1) document type, (2) subject area, (3) author, and (4) country of publication. The study’s results reflect the research 6G community’s trends, highlight important research challenges, and elucidate potential directions for future research in this interesting area.